For a Scenic Lighting Pedagogy: what are we talking about? (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This text has as its theme the teaching of Scenic Lighting. To articulate it, the authors proposed a reflection on the use of the expression Scenic Lighting Pedagogy, from an intersection with ideas of Theater Pedagogy. The aim of this text is to call on professionals and artists in the area to produce other reflections on the discussion raised. For this, a brief analysis is raised about the presence of Scenic Lighting in the teaching of the Performing Arts and Staging Production.